Eco-friendly carbonized molasses powder as filler in natural rubber vulcanizate / Siti Jannatul Sakinah Jamaluddin - Jamaluddin, Siti Jannatul Sakinah (2020)
Further researchers has been carried out to utilize carbonized molasses as possible filler to replace carbon black in order to reduced environmental problem and provide substitution of synthetic filler with natural filler. Study of carbonized molasses had undergone carbonization process to produce natural filler that have comparable properties as carbon black. The research also focus on minimization the usage of carbon black as it has high tendency to deplete and dangerous for environment and human health. Therefore, natural filler is introduce to replace or minimized the usage of carbon black in the rubber industry. Characterization of carbonized molasses is observed by using FTIR. It was found that, carbonized molasses has quite same properties as carbon black in which carbonized molasses contain similar functional group as carbon black. It shows that, carbonized molasses is suitable to be used with carbon black. This is because, they has good filler- rubber relationship and can formed a good reinforcement effect on vulcanized natural rubber. The rubber compound has been reinforced with carbonized molasses and carbon black has been produced using two-roll mill and vulcanized using hot press at 170 ºC. This study has been done to determine the effect of various amounts carbonized molasses compared with carbon black on its behavior. On top of that, there are three types of test has been carried out. Firstly, mechanical test such as tensile test to determined tensile strength, elongation at break, tensile modulus. Secondly, physical test such as hardness and swelling test. Thirdly, cure characteristic such as optimum cure time, t90 has been carried out. Based on the data results, it shows that, the incorporation of carbonized molasses (50%) with carbon black (50%) has the highest mechanical properties in term of tensile strength, tensile modulus and elongation at break. Moreover, in term of physical properties, it also has highest hardness, Mooney viscosity and swelling resistance. On top of that, in term of cure characteristic, it also has good cure characteristic. To sum up, carbonized molasses has a good reinforcement effect and can be used to replace carbon black up to 50% which means it can partially use to replace carbon black.